Обгрунтування вимог до методів генерування псевдовипадкових послідовностей - Гріненко, Т. О.; Мордвінов, Р. І. (ХНУРЭ, 2011)
It is grounded requirements to pseudorandom number generators. The research results concerning provided methods are based on hash functions, block cipher algorithms and number theoretic problems.
Keywords: Генератори випадкових чисел; генерування ключів